QSAR and DFT Studies on Non-Linear Optical Properties of Some Schiff Bases Derived from Salicylaldehyde and Nitroanilines - Hagar, Mohamed; Soliman, Saied M.; Massoud, Raghdaa A.; Zaid, Mohamed M. (Asian Journal of Chemistry, 2015)
QSAR on the non-linear optical properties of some Schiff bases derived from salicylaldehyde and nitroanilines have been performed. All the studied structures are noncentrosymmetric with C1 point group, hence are second harmonic generation (SHG) active. Quantum chemical parameters such as polarizability (a0), hyperpolarizability (btot) and the frontier molecular orbital energy gap (DE) were used in this study. The separate stepwise selection-based multiple linear regression (MLR) analyses were performed using these descriptors. The selected multiple linear regression equations, those having the highest correlation coefficient values (R2 > 0.9), showed the importance of the polarizability and energy gap quantum chemical parameters on the second harmonic generation values of the studied compounds. The hyperpolarizability showed almost insignificant improvement to the correlation coefficient (R2). It could be seen from the best multiple linear regression equation (R2 = 0.955) that there is enhancement in the second harmonic generation values with the decrease of a0. The opposite is true for the energy gap (DE).